Mesenchymal Stromal Cell-Conditioned Medium for Skin Diseases: A Systematic Review - Montero-Vilchez, Trinidad; Sierra-Sánchez, Álvaro; Sanchez-Diaz, Manuel; Quiñones-Vico, Maria Isabel; Sanabria-de-la-Torre, Raquel; Martinez-Lopez, Antonio; Arias-Santiago, Salvador (Frontiers in Cell and Developmental Biology, 2021)
The skin is the largest organ of the human body and its dysfunction is related to many diseases. There is a need to find new potential effective therapies for some skin conditions such as inflammatory diseases, wound healing or hair restoration. Mesenchymal stromal cells (MSCs)- conditioned medium (CM) provide a potential opportunity in the treatment of skin disease. Thus, the objective of this review is to evaluate the uses of MSCs-CM for treating skin diseases both in animal and human models. A systematic review was conducted regarding the use of MSCs-CM for treating skin conditions. One hundred and one studies were analysed. MSCs-CM was evaluated in wound healing (55), hypertrophic scars (9), flap reperfusion (4), hair restoration (15), skin rejuvenation (15) and inflammatory skin diseases (3). MSCs-CM was obtained from different MSC sources, mainly adipose tissue, bone marrow and umbilical cord blood. MSCs-CM was tested intravenously, intraperitoneally, subcutaneously, intradermally or intralesional injected or topically applied. MSCs-CM was used in both animals and humans. MSCs-CM improved wound healing, hair restoration, skin rejuvenation, atopic dermatitis and psoriasis both in animals and humans. MSCs-CM also decreased hypertrophic scars and flap ischemia in animal models. In conclusion, MSCs-CM is a promising therapy for skin conditions. Further studies are needed to corroborate safety and effectiveness and to standardize CM manufacturing.